(untitled) (Journal of Dhaka Medical College, 2011)
Context: The spleen is the largest lymphoid organ in the human body. The morphology of spleen is affected by number of disorders, e.g. abnormalities of the cells, which populate within the spleen or disturbance of its storage function. Therefore, the size of the spleen can be regarded as an indicator of the disease process. Study design: Cross-sectional, descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka, from August 2005 to June 2006. Materials: The present study was performed on 70 postmortem human spleens collected from unclaimed dead bodies which were under autopsy examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. Methods: The samples were divided into six different age groups i.e. group A (0–19 years), B (20–29 years), C (30–39 years), D (40–49 years), E (50–59 years) and F (>60 years). The length, breadth and thickness of the spleen were measured. The number of the notch in its upper and lower poles was observed. The presence of any accessory spleen was also observed in situ. Results: The length, breadth and thickness of the spleen were found to have no significant changes with advancing age. Notches were present on the upper border of spleen in 88.57% of samples and lower border of the spleen in 27.14% of samples. Accessory spleen was found in 24.28% of cases. Key words: Human spleen; length; breadth; thickness; splenic notch; accessory spleen. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8569 J Dhaka Med Coll. 2011; 20(1) :32-36